Liability for Illegal Human Trafficking: a Comparative Characteristics - Stratonov, Vasyl; Rakova, Yulia (Archives of Criminology and Forensic Sciences, 2022)
The research paper analyses the legislation of Anglo-Saxon and Romano-Germanic Legal Systems devoted to the issue of illegal human trafficking. A comparative characterization of Ukrainian legislation in the field of human trafficking with the criminal law norms of European countries has been carried out. The provisions of responsibility for illegal human trafficking in the countries of the Anglo-Saxon Legal System have been carried out. It has been found that the concept of “human trafficking” is not universal, each country uses its own version of this criminal activity. There is also no unified point of view regarding the understanding and definition of the concept of “human trafficking” because the studied criminal acts often do not indicate the execution of purchase and sale agreements, other agreements regarding a person, and even recruitment. Therefore, the conducted comparative characteristics make it possible to actualize issues that, according to the authors, can serve as a further basis for further scientific research and improvement of the legislation, and thus improve the activity of law enforcement agencies, which in general will lead to an improvement in the protection of human rights